Perceptions about malaria among the Bedia tribal people in Uttar-Dinajpur district of West Bengal, India - Paul, Uttam Kumar; Bhattacharyya, Pramukh; Bhattacharyya, Rituparna; Bandyopadhyay, Arup (International Journal of Research in Medical Sciences, 2017)
Background: In a tropical country like India, malaria is a major vector borne disease ranging from highly urbanised to deep rural areas. Though lots of health activities are going on against it in urban areas it is difficult to penetrate the deep rural areas particularly the tribal based interior villages because of lack of initiative, huge illiteracy, gross poverty and language problems. Therefore, a study was ventured in a rural community in North Dinajpur district of West Bengal, India occupied by members of scheduled tribe called ’Bedia’ whose mother tongue is a tribal language called ’Nagori’- to understand their knowledge and perceptions about malaria so that future actions can be taken to uplift their health status and awareness particularly in relation to malaria. Methods: Present study have conducted three focus group discussions (FGDs), one with male participants, one with females and the third one involving both the sexes. There were 9-11 participants per FGD and total of 28 participants were included in the study. Results: The transcripts were at first coded and then categories were framed. Total six categories, which are: perceived causes of malaria, perceived features of malaria, mode of spread, treatment, difficulties and modes of prevention. After the content analysis of the transcripts conclusion was drawn. Conclusions: Through our field work and the focus group discussions on the Bedia tribes we understood several misconceptions and lack of awareness of the tribal community about malaria. However, it was possible to create awareness and confidence among them that they could take all preventive measures and positive approaches towards malaria.